CONCEPTUAL MODEL IN INTEGRATED MARKETING COMMUNICATION - Šķiltere, Daina; Bormane, Santa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Integrated marketing communications are developing, with IMC approaches to communication with consumers seeing further enhancements in the scientific literature. However, in order to reach the marketing targets, a variety of IMC tools may be used in combination when implementing marketing activities. Despite each IMC tool in itself being highly distinctive, they all depend on each other in the creation of product consumption value and the enhancement of economic, communicational and social benefits. Purpose of the paper: The goal of the research is to assess the integrated marketing communications used in the marketing strategy of Latvian food retail chains. Methodology/methods: The following scientific research methods are used in the research study: analytical, comparative, graphical, statistical, observatory and interrogative. The research focuses on the Latvian food retail sector, with leading specialists from all Latvian food retail chains polled. The object of the research is Latvian food retail chains, and the subject of the research is integrated marketing communication as a set of tools. Findings: The results of the research are of both theoretical and practical value, as it confirmed the hypothesis that a complex use of IMC promotes a long-term relationship among all stakeholders of the selling and buying process. The authors have collected and classified IMC tools and, based on the results of the research, drawn up a conceptual model of integrated marketing communications.